The Kurdish Factor in the Foreign Policies of Turkey and Iran - Ochilkhonov, Abdulazizkhon (Pubmedia Social Sciences and Humanities, 2025)
This article analyzes the historical formation of the “Kurdish factor” in the foreign policies of Turkey and Iran, as well as its impact and consequences for state security. The study explores the trajectory from the Treaty of Sèvres and the Treaty of Lausanne to the transnational demographic weight of the Kurds, the activities of the PKK and PJAK, the dynamics of the Kurdish diaspora, and Turkey’s operations in Syria and Iraq (Euphrates Shield, Olive Branch, Peace Spring, Claw-Sword) within the context of the AKP’s democratic opening initiatives. Regarding Iran, the article highlights pragmatic relations with the Kurdistan Regional Government (KRG), resource geopolitics, the Sunni–Shia dimension, and the paradigm of “domestic security” as central concepts. The paper also discusses legitimization discourses that rely on Article 51 of the UN Charter and UN Security Council resolutions, and it proposes an integrated model of political, legal, and economic approaches for regional stability. The analysis demonstrates that the Kurdish issue cannot be resolved solely through military measures; instead, reducing economic inequality, recognizing cultural rights, and fostering transnational cooperation are essential pathways.